Studi Penciptaan Game Komputer Pembelajaran Perbendaharaan Kata Budaya - Rachman, Anung (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2010)
Mastery of multimedia applications, content, and aesthetics is an integral Trichotomy in the design of inter-active learning games. All three must function in proportion if a developer of multimedia applications to achieve optimal results in education. In this study the learning game was created by local cultural vocabulary. The work is the result of a combination of educational content of local culture and aesthetics of multimedia.The work of "game culture" not only offers information about culture, but further, this work aims to provide learning using a humanistic ap-proach. Lessons are presented in the form of multimedia games and animations intended to be a beauty to the learner to display the difference to the lesson as usual. Key words: games, animation, local culture